2021
DOI: 10.3390/polym13203519
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Characterization of Thin PEDOT:PSS Films on Alumina and Thiol–Ene Substrates

Abstract: Transparent polymer layers that heal minor scratches and maintain the optical properties of the devices for a long time are highly desirable in optoelectronics. This paper presents the results of the electrical characterization of thin PEDOT:PSS films on the novel, optically transparent thiol–ene substrates capable of healing scratches under room-temperature conditions. Electrical properties of the PEDOT:PSS films deposited on the conventional alumina ceramic substrates were also tested for comparative purpose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…In fact, it was reported that higher surface roughness leads to higher electrical resistance. [ 64,65 ] In Figure 8, it can be observed that the reduction of electrical resistance (from 66.9 to 8 M Ω) due to thickness increase is also followed by the reduction of the standard deviation (from 34.3 to 1.6 M Ω) (Figure 8a). This confirms the hypothesis that higher film thickness allows improving the electrical parameters of the system due to reducing the effect of high roughness values (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, it was reported that higher surface roughness leads to higher electrical resistance. [ 64,65 ] In Figure 8, it can be observed that the reduction of electrical resistance (from 66.9 to 8 M Ω) due to thickness increase is also followed by the reduction of the standard deviation (from 34.3 to 1.6 M Ω) (Figure 8a). This confirms the hypothesis that higher film thickness allows improving the electrical parameters of the system due to reducing the effect of high roughness values (Figure 8b).…”
Section: Resultsmentioning
confidence: 99%